Childhood obesity and the incidence of dental caries (Research, Society and Development, 2023)
This study aims to identify the correlation between childhood obesity and dental caries in early childhood, considering etiological factors and common characteristics, and to examine the incidence of dental caries in obese children described in academic literature. The current study was conducted in November 2022 in database: PubMed, Latin American and Caribbean Health Sciences Literature (LILACS) and MedLine. The descriptors used were Obesity, Child Health, and Dental Caries, using the Boolean operator “AND”. There were 255 articles that matched the search, 38 were selected based on the title, after their full reading and having applied the inclusion and exclusion criteria, 20 articles were included in the composition of the literature revision. In the studies was found a complex comparison between obese children and dental caries, moderated by sociodemographic conditions, evincing that modulator factors of dental caries such as health education and oral hygiene are of extreme relevance. Although they share etiological factors, there isn’t a direct correlation between early childhood dental caries and childhood obesity, due to the correlation of dental caries not only with nutritional status, but also with the quality and quantity of oral hygiene, level of education and the child’s diet. It is necessary a multidisciplinary action and conduct new studies that would involve a larger sample under certain modulator circumstances: socioeconomic, psychosocial, nutrition and oral hygiene.